Contribution of vascular smooth muscle cell apoptosis to spiral artery remodeling in early human pregnancy. (24th March 2022) - Liu, Hanbo; Ning, Fen; Lash, Gendie E.
Abstract: Uterine spiral artery remodeling is one of the key maternal adaptations of pregnancy, allowing delivery of the large volumes of maternal blood required for both placental and fetal growth. Failure of this process is associated with obstetric complications including preeclampsia, fetal growth restriction and miscarriage. Spiral artery remodeling is characterized by loss of the musculoelastic wall which is replaced by fibrinoid and intramural extravillous trophoblast cells (EVT). In recent years attention has focused on the initial stages of spiral artery remodeling which include separation of the vascular smooth muscle cells (VSMCs) and their phenotypic switch to a more synthetic phenotype, facilitating their migration away from the vessel wall. However, less is known about the final fate of the VSMCs. In vitro studies suggested that EVT could induce VSMC apoptosis, though VSMC apoptosis is not seen within the wall of the spiral arteries undergoing remodeling. However, apoptotic VSMCs have been observed amongst those cells which had migrated away from the vessel wall. This review article gives a brief overview of the current state of knowledge of the processes involved in spiral artery remodeling, and then concentrates on the mechanisms involved in VSMC apoptosis, drawing on knowledge from other vascular beds. Highlights: Spiral artery remodeling is critical for successful pregnancy. Spiral artery remodeling involves in complete loss of the VSMC layer. Apoptosis of VSMCs within the vascular wall is a rare event. Once VSMCs have phenotypically switched to more synthetic, they are then prone to apoptotic signals.